Chemical and Mineralogical Characterization of the Clayey Sands of Samo and Bingerville in the North of the Lagoon Fault, South of the Ivory Coast, In Road Construction - Kouassi, Kouakou Pierre; Sosthène Ronald, Atto Yapi Désiré; Athanase, Konin; Martial, Grehoa Abalé (European Scientific Journal, ESJ, 2023)
In Côte d’Ivoire, particularly in the south, the majority of paved and unpaved roads are made of clayey sand, given its availability. However, the early degradation of roads related to a strong sensitivity of this material to the environment (climate, geology and degrees of alteration) and a poor knowledge of the geotechnical properties of this one could slow down their use in road construction. It is within this framework that the work undertaken aims at determining the chemico-mineralogical nature of the clayey sands of the localities of Bingerville and Samo, in the South-East of Côte d’Ivoire. Tests were carried out taking into account the chemical and mineralogical analyses. Chemical elements were determined by atomic absorption spectrometry, colorimetry, complexometry and gravimetry. The determination of organic matter was determined using the Rock-Eval 6 pyrolysis method. The mineralogical composition was determined using a Bruker D8 ADVANCE diffractometer. The chemico-mineralogical analyses show that the clayey sands of Bingerville and Samo are more enriched in silica oxide (SiO2) but less enriched in iron oxide (Fe2O3). All the soils studied have an S/R ratio greater than 2, indicating that these soils are non-lateritic. In addition, the low TOC values between 0.1 and 0.15% by weight, which reflect the extremely low amount of organic matter in these soils, show the possibility of treating these soils with hydraulic binders. In addition, the mineralogy of the studied soils indicates that they are mainly composed of kaolinite and illite.